Implementation of Risk Management in Bank Syariah Mandiri Griya Financing Products - Zumrotun Nazia; Nanang A. Daud (Perisai : Islamic Banking and Finance Journal, 2022)
This study aims to determine the implementation of risk management in the financing products of the Mandiri Griya Islamic Bank. This research uses a descriptive qualitative method with a field study approach, as well as in-depth interviews with informants. The results of this study indicate that the implementation of risk management on BSM Griya financing products at BSM KCP Malang Turen has been in accordance with the guidelines and provisions imposed by the BSM head office. As for what has been done by BSM KCP Malang in managing risk on BSM Griya products, among others, first starting with identifying risks, risk assessment and also risk control, then each implementation is reported to the head office. BSM KCP Malang Turen also conducts an online system in an effort to minimize the risk of financing and bank operations. Meanwhile, the problem of human resources is an obstacle in the implementation of BSM Griya financing. The steps for handling non-performing financing for the BSM Griya product are carried out by first identifying the customer's journey, and in terms of collectibility for further action by the bank.